THE IMPACT OF VITAMIN D AND INSULIN ON HUMAN METABOLIC HEALTH - M. R. Umarova; Sh. K. Yusupova; M. K. Matkarimova; M. I. Soliyeva (Web of Journals Publishing, 2024)
This article is dedicated to studying the complex relationship between Type 2 diabetes and metabolic health. It analyzes the interconnection between Vitamin D and insulin and how these factors influence the development of diabetes. Research suggests that Vitamin D deficiency may increase insulin resistance and the risk of diabetes. The article also discusses the positive effects of Vitamin D on metabolic processes and its role in the prevention of diabetes. It emphasizes the need for further research to confirm these relationships more precisely.
Keywords: Type 2 diabetes, Vitamin D, insulin, metabolic health, insulin resistance, diabetes prevention, glucose levels.